2021
DOI: 10.3390/su132313213
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and Parents’ Perceptions of Barriers to Cycling to School—An Analysis by Gender

Abstract: Internationally, there is increased emphasis on the need to reduce dependency on cars and to encourage more sustainable forms of travel, including active travel. To encourage increased levels of cycling, the focus has generally been on improving cycling infrastructure and on making cycling safer. While cycling rates have increased in many countries, including Ireland, women are often less likely to cycle than men. While there are some notable exceptions to this (for example, in the Netherlands) this phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The research on children's school travel behavior through school started late in China, and the research results are also relatively limited. In the existing literature, research on personal factors mainly includes age ( 11 – 14 ), gender ( 13 , 15 18 ), race ( 19 21 ), etc. Family factors mainly include family income ( 22 25 ), family car ownership rate ( 26 29 ), family driver's license ownership rate, parents' convenience of transportation ( 12 , 30 , 31 ), parents' attitude toward students' travel ( 16 , 32 34 ), number of brothers and sisters ( 32 , 35 ), parents' education level ( 20 , 29 ) and other family factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research on children's school travel behavior through school started late in China, and the research results are also relatively limited. In the existing literature, research on personal factors mainly includes age ( 11 – 14 ), gender ( 13 , 15 18 ), race ( 19 21 ), etc. Family factors mainly include family income ( 22 25 ), family car ownership rate ( 26 29 ), family driver's license ownership rate, parents' convenience of transportation ( 12 , 30 , 31 ), parents' attitude toward students' travel ( 16 , 32 34 ), number of brothers and sisters ( 32 , 35 ), parents' education level ( 20 , 29 ) and other family factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study from Taiwan showed that good network connectivity was favorable for AT. Studies by Tuber and Sudeck (2021) and Higgins and Ahren (2021) showed that safety during walking or biking was an important factor influencing AT use in Germany and Ireland [49,50]. Tuber and Sudeck (2021) showed better security from neighborhood crimes enhanced the willingness of a student to walk to school.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tuber and Sudeck (2021) showed better security from neighborhood crimes enhanced the willingness of a student to walk to school. Higgins and Ahren (2021) showed if safety from crime and vandalism can be ensured, people will use their bicylces more often [50]. Tuber and Sudeck (2021) revealed that when students were safe from vehicular traffic, their frequency to bicycle to school increased [49].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite these benefits, bicycle modal share remains low on many U.S. universities campuses, influenced by a lack of cycling infrastructure, societal norms, and the dimension of race. Transportation planners are searching for ways to bolster cycling at university campuses [5] [14] [15]. The various barriers that can prevent people from cycling include physical obstacles and societal perceptions.…”
Section: Introductionmentioning
confidence: 99%